ANGGOTA LEGISLATIF ADALAH DPR DAN PRESIDEN - Cherlyne Baby Florencia; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2022)
There are several institutions in Indonesia.Indonesia adheres to a presidential system ofgovernment. In a presidential system, the head of government and head of state is the president.The institutions in the government order are the legislative, executive, and judicial. In carrying outhis duties the president is assisted by these institutions. In Indonesia, it is the DPR together withthe President that forms the law. The purpose of this study is to determine the position of the DPRand the President in the government system and to find out the pattern of the relationship betweenthe DPR and the President in carrying out legislative functions in Indonesia. The method in thisresearch is normative juridical. The results of the study show that the DPR together with thePresident have an equal position in carrying out their duties to form laws.